Flexibility of the labour market as a determinant of development degree of selected EU countries - Blažević Dević, Ivona; Požega, Željko; Ježić, Zoran (Serbian Journal of Management, 2025)
With the aim of evaluating the impact of integrating flexible forms of work on the economic development of the observed EU countries, the authors investigated and systematically analyzed the connection between the criterion variable labour market flexibility and the predictor variable gross domestic product per inhabitant. The authors conducted the research on the EU LFS official data set obtained based on the RPP 35/2020-LFS project approved by the European Commission and Eurostat. The paper will analyze a sample of 321.208 respondents in the period from 2008 to 2018 in Bulgaria, Greece, Croatia and Romania. In the research part of the work, authors used linear correlation analysis, the correlation coefficient and coefficient of determination were calculated, statistical significance was associated, and for the purposes of statistical analysis, authors also used statistical programs SPSS and Statistica. Based on an extensive analysis of data from selected European Union member states, author obtained results that indicate an increase in the dynamics of the labour market and growth of the gross domestic product per inhabitant in 75% of the observed countries, which authors implied by the greater flexibility of the labour market.